Comprehensive Examination to Enhance Student Competence in Accounting - Asri, Marselinus (Lumbung Pare Cendekia, 2024)
The study aimed to evaluate the effectiveness of comprehensive examinations in enhancing the skills of accounting students at Universitas Atma Jaya Makassar (UAJM), focusing on their understanding and application of basic accounting principles. Despite their importance, comprehensive exams often cause significant stress for students, and there is evidence that many students have difficulty applying concepts theory into practice. This study aims to identify specific areas of confusion and suggest improvements in testing processes and teaching methods. A qualitative research design was used, with participation from 33 students, faculty, parents, employers, and alumni. Data were collected through in-depth testing, interviews, and observations. Thematic analysis is used to analyze data and identify common themes and patterns. Research shows that while comprehensive exams play an important role in ensuring a thorough understanding of accounting principles, students face challenges with stress-related knowledge and apply the concepts in practice. Students and faculty emphasized the need for more real-world examples, interactive learning activities, and continuous assessment. Employers and alumni confirm the effectiveness of the exams but also emphasize the need for more hands-on learning sessions. To improve the effectiveness of comprehensive exams and accounting education at UAJM, the study recommends incorporating real-world examples, case studies, learning activities interactive exercises in the program. Ongoing assessment and feedback should be provided throughout the semester. Additionally, exam stress management strategies should be implemented to improve students' academic performance and health.